Large scale deletions in the GPC3 gene may account for a minority of cases of Simpson-Golabi-Behmel syndrome. Issue 6 (June 1997) - Lindsay, S; Ireland, M; O'Brien, O; Clayton-Smith, J; Hurst, J A; Mann, J; Cole, T; Sampson, J; Slaney, S; Schlessinger, D; Burn, J; Pilia, G
Abstract : AIMS OF THE STUDY: To identify the proportion and type of deletions present in the glypican 3 (GPC3) gene in a group of patients with Simpson-Golabi-Behmel syndrome (SGBS). SUBJECTS AND METHODS: PCR analysis using primer pairs which amplify fragments from each of the eight exons of the GPC3 gene was carried out in a series of 18 families with SGBS (approximately half of reported cases). RESULTS: Deletions were detected in only five families (one reported previously). We found deletions in all exons of the gene except exon 3. CONCLUSIONS: Our results suggest that large scale deletions may be less common in SGBS than was originally thought. One patient, with an exon 4 and 5 deletion, lacked the characteristic facial dysmorphic features. This raises the possibility of involvement of GPC3 gene defects in a wider range of overgrowth disorders.